Can Better Emotion Regulation Protect Against Interpersonal Violence in Homeless Youth Social Networks?. Issue 11 (June 2021) - Petering, Robin; Barr, Nicholas; Rice, Eric
Homeless youth experience all types of violence at higher rates than their housed counterparts. This is typically the result of many contributing factors including childhood experiences of trauma, subsistence survival strategies, and exposure to perpetrators while living on the streets. Reducing violence in the lives of homeless youth is imperative and can contribute to a young person's ability to safely and successfully exit the streets and lead a long and productive life in society. However, developing public health and social interventions to reduce violence in adolescent and young adult populations is difficult due to the complex interplay of extrinsic and intrinsic drivers of this phenomenon. Los Angeles area homeless youth ( N = 366) were asked questions regarding recent violence experiences, emotion regulation, and their social network. Multivariable logistic regressions tested the overall effect of emotion regulation on violence, controlling for age, gender, race, sexual identity, experience of childhood abuse, and data collection site. In this sample, 56% of youth endorsed fighting in the previous year, and those who reported more difficulties with emotion regulation were significantly more likely to fight. In addition, youth who scored below the mean on difficulties with regulation and belonged to networks characterized by low-difficulty peers were 60% less likely to report fighting. Emotion regulation skills represent a malleable target for intervention that may contribute to reduced propensity for violence in this population. Implications for network-based interventions to improve individual emotion regulation and reduce overall violence among homeless youth and other at-risk populations are discussed.